(untitled) (Indonesian Minority Justice Review, 2024)
This paper explores Indonesia’s legal framework for preserving indigenous languages and traditions, emphasizing the intersection of cultural rights and justice. Indigenous communities in Indonesia possess a rich cultural heritage, including unique languages, rituals, and knowledge systems, yet these are often at risk due to modernization, development projects, and the dominance of the national culture. The study reviews national and regional legal provisions aimed at protecting cultural heritage, including the 2001 Law on the Protection of Cultural Heritage and the 2019 Law on National Languages. Through legal analysis and case studies, the paper examines how effectively these laws have been implemented to safeguard indigenous languages and traditions. It also investigates the tensions between state-driven development, educational policies, and indigenous cultural rights. The findings suggest that while the legal framework offers some protections, implementation remains inconsistent, and indigenous communities often face pressures to conform to the dominant national culture. The paper argues for a more inclusive approach to cultural rights, where the preservation of indigenous languages and traditions is not merely symbolic but actively supported through education, legal recognition, and community empowerment. It concludes by advocating for stronger legal protections, increased political representation of indigenous groups, and more robust state commitment to cultural diversity.